Phylogenetic relationships of leaf monkeys (Presbytis; Colobinae) based on cytochrome b and 12S rRNA genes - Vun, V.F.; Mahani, M.C.; Lakim, Maklarin; Ampeng, A.; Md Zain, Badrul Munir (UNPEC-RP, 2011)
Little is known about the classification and phylogenetic relationships of the leaf monkeys (Presbytis). We analyzed mitochondrial DNA sequences of cytochrome b (Cyt b) and 12S rRNA to determine the phylogenetic relationships of the genus Presbytis. Gene fragments of 388 and 371 bp of Cyt b and 12S rRNA, respectively, were sequenced from samples of Presbytis melalophos (subspecies femoralis, siamensis, robinsoni, and chrysomelas), P. rubicunda and P. hosei. The genus Trachypithecus (Cercopithecidae) was used as an outgroup. The Cyt b NJ and MP phylogeny trees showed P. m. chrysomelas to be the most primitive, followed by P. hosei, whereas 12S rRNA tree topology only indicated that these two species have close relationships with the other members of the genus. In our analysis, chrysomelas, previously classified as a subspecies of P. melalophos, was not included in either the P. m. femoralis clade or the P. m. siamensis clade. Whether or not there should be a separation at the species level remains to be clarified. The tree topologies also showed that P. m. siamensis is paraphyletic with P. m. robinsoni, and P. m. femoralis with P. rubicunda, in two different clades. Cyt b and 12S rRNA are good gene candidates for the study of phylogenetic relationships at the species level. However, the systematic relationships of some subspecies in this genus remain unclear.